The Role of Society in Increasing Voter Participation in Pilkada in Kab. Deli Serdang - Boby Indra Prayoga; Mahyudin Situmeang; El Azhari (International Conferences SDGs 2030 Challenges and Solutions, 2030)
The participation of the community in increasing voter participation in theelection of regional head elected by regional head election, can be considered orviewed as social problem in society, of course, the social problem has its owncause for the society itself.